Deviations of mental status of compulsory settlers from ATO area in dependence on temporal dynamics - Polyschuk Victoria (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
In the article under consideration was analyzed the notion of "compulsory settling" and main mental problems people of this category face; was investigated mental state of compulsory sellers who live on the dole and on their own money; was investigated the influence on the mental health of compulsory settlers of the next factors: age, employment/unemployment, marital status, renting of the apartment/ living in the state Sanatorium, adaptability, level of self-esteem and level of personal aims.
Keywords: internal settler; post traumatic stress disorder; adaptability; self-esteem; personal aims; psychopathology challenges